Influence of surgical resection no plasma Endoglin (CD105) level in non-small cell lung cancer patients - Kopczynska, E.; Dancewicz, M.; Kowalewski, J.; Makarewicz, R.; Kardymowicz, H.; Kaczmarczyk, A.; Tyrakowski, T. (Experimental Oncology, 2012)
Background and Aim: Endoglin is a proliferation-associated antigen on endothelial cells and essential for angiogenesis. Soluble endoglin (s‑endoglin), formed by proteolytic cleavage of ectodomain of membrane receptor could be an indicator of tumor‑activated endothelium. The aim of present study was to analyze changes of s‑endoglin level in plasma of lung cancer patients following surgical resection and to estimate the correlation of s‑endoglin with other soluble receptors, sTie2 and sVEGF R1. Patients and Methods: The study group consisted of 37 patients with stage I of non-small cell lung cancer. Plasma concentrations of s‑endoglin, sTie2 and sVEGF R1 were evaluated by ELISA, three times: before surgical resection and on postoperative day 7 and 30. Results: The median of s‑endoglin concentration decreased significantly on postoperative day 7 when compared with preoperative level and next increased on 30th day and it was comparable with that before surgery. s-Endoglin correlated with another soluble receptors, with sTie2 both before surgery (r=0.44) and on postoperative day 7 (r=0.52) and on 30th day (r=0.58), with sVEGF R1 — only on postoperative day 7 (r=0.75). Conclusion: The increased level of serum endoglin in lung cancer patients compared to controls and its changes after surgical treatment suggest potential application of soluble form of endoglin as potential tumor marker.